Elective repeat caesarean section versus induction of labour for women with a previous caesarean birth - Dodd, Jodie M (Cochrane Database Syst Rev, 2017)
BACKGROUND: When a woman has had a previous caesarean birth and requires induction of labour for a subsequent pregnancy, two options are available for her care: an elective repeat caesarean and planned induction of labour. Although risks and benefits are associated with both elective repeat caesarean birth and planned induction of labour, current sources of information are limited to non‐randomised cohort studies, and studies designed in this way have significant potential for bias. Consequently, any conclusions based on results of these studies are limited in their reliability and should be interpreted with caution. OBJECTIVES: To assess, using the best available evidence, the benefits and harms of a policy of planned elective repeat caesarean section versus a policy of induction of labour for women with a previous caesarean birth who require induction of labour for a subsequent pregnancy. Primary outcomes include success of induction of labour, need for caesarean section, maternal and neonatal mortality, and maternal and neonatal morbidity. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Trials Register (31 May 2017) and planned to search reference lists of retrieved studies. SELECTION CRITERIA: Randomised controlled trials with reported data on comparison of outcomes in mothers and babies between women who planned an elective repeat caesarean section and women who planned induction of labour when a previous birth was performed by caesarean. Cluster trials and quasi‐randomised trials were also eligible for inclusion. We would consider trials published only as abstracts if they provided enough information to meet review inclusion criteria. DATA COLLECTION AND ANALYSIS: We performed no data extraction. For future updates, if randomised controlled trials are identified, two review authors will independently assess trials for inclusion and risk of bias, and will extract data and check extracted data for accuracy. Review authors will assess the quality of the evidence using the GRADE approach. MAIN RESULTS: Review authors identified no randomised controlled trials. AUTHORS' CONCLUSIONS: Both planned elective repeat caesarean section and planned induction of labour for women with a prior caesarean birth are associated with benefits and harms. Evidence for these care practices has been drawn from non‐randomised studies, which are associated with potential bias. Therefore, any results and conclusions presented must be interpreted with caution. Randomised controlled trials are required to provide the most reliable evidence regarding the benefits and harms of both planned elective repeat caesarean section and planned induction of labour for women with a previous caesarean birth.